Future climate assessment in the Mediterranean region using downscaled CMIP6 data - Daher, Houraa; Kirtman, Ben P. (Frontiers in Climate, 2025)
Due to the anthropogenic increase in greenhouse gas and aerosol forcing, the Mediterranean has been labeled a “climate change hot spot.” Previous studies have shown that climate change has dire consequences on socioeconomic situations in the Mediterranean region. Ten high-resolution global coupled climate models and two climate emissions scenarios are analyzed from the Bias Correction Constructed Analogs with Quantile mapping reordering dataset, which is downscaled CMIP6 data. Daily precipitation and air-temperature data from both the wet and dry season is used to calculate droughts and heatwaves in the Mediterranean region, including the Middle East and North Africa countries. As expected, larger impacts are observed in the high emissions scenario and during the dry season for both droughts and heatwaves. Comparing the wet season to the dry season droughts, there is a northward shift in the positive signal as most of the values are seen over the Mediterranean Sea in the wet season and over the northern Mediterranean and Europe in the dry season. For the heatwaves, the dry season shows a response stronger than the one observed by the wet season by nearly two times, and there is a strong signal located over the Mediterranean Sea during the dry season that is not seen during the wet season.